Mortality and Diseases Status in Layer Chicken Flocks Reared in Traditional Farms in Khartoum-Sudan - Babiker, M.A.; Tawfeig, A.; Yahia, I.E.; Noura, K. (International Journal of Poultry Science, 2009)
Ten poultry flocks of layer chicks were followed up and monitored during the first 16 weeks in Khartoum-Sudan. The management, diseases status and the mortality during this period were recorded. through direct visits. Each flock was visited at least once a week. Information were collected from a veterinarian supervising the flock and the flock owner as well using data sheet and semi-structured interview. The management including housing, hygiene measures, vaccination practices, diseases occurred and mortality were observed and recorded. The diseases and conditions causing mortality were found to be; Newcastle Disease (ND), Infectious Bursal Disease (IBD), Salmonellosis, Coccidiosis, Chronic Respiratory Disease (CRD), Tape Worms and different physical conditions (accidental death) which occupied 41.24, 25.9, 2.6, 4.93, 1.84, 1.66 and 11.42% of the total mortality respectively. These diseases caused mortality rates ranged as follows: ND = 7.77-43.47%, IBD = 16.32-24.44%, Salmonellosis = 1.6-10.78%, CRD = 1.11-5.59%, Coccidiosis = 2.88-6.41%, Tape Worms = 0.2-5.5% and physical conditions = 0.56-10.88%.